Reformasi Maqashid Syariah Klasik Menuju Perspektif Kontemporer - Abd Wahid (STAI Syaichona Moh. Cholil Bangkalan, 2018)
Constructive formulation of Islamic jurisprudence is often deadlocked in addressing contemporary social problems so it demands the birth of reformulation efforts towards understanding and interpreting Islamic teachings not only in the field of jurisprudence but also about fiqh proposals including the term Maqashid Syariah. The traditional or classical Maqashid concept has limitations and disadvantages as follows: its range is partial, individualistic, and limited in terms of its induction and generality. The classical maqashid sharia reformation towards a contemporary perspective is done by renovating the following things: improvements in the reach, subject, and induction of traditional maqashid. The classifications of contemporary maqashid are general Maqashid (al-Maqashid al-‘ammah), special Maqashid (al-Maqashid al-Khassah), and partial Maqashid (al-maqashid al-juz’iyyah); reforms from 'safeguard' and 'protection' goals to 'development' and 'human rights'. The purpose of this perspective reform is to be able to respond to global issues, and develop from just 'wisdom behind legal decisions' to practical plans for reform and reform.